Algoritma Apriori Untuk Penentuan Assosiasi Penjualan Barang - Calvin Ivan Wiryawan; Yustina Retno Wahyu Utami; Didik Nugroho (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2021)
The increasing of selling basic needs make the company has to provide a lot of goods. The data will be growing up with increasing the transaction at Sari Bumi store. All this time, the selling basic needs at Sari Bumi Store unstructured well so that needed an application with produce important information that can decide marketing strategies. In this research, Apriori algorithm is used to determine association rules. This method was chosen because it is one of the classic data mining algorithms to look for patterns of relationships between one or more items in one dataset. A priori algorithms can help companies in developing marketing strategies. The result of this research is combination between 4 item set with a minimum support of 30% and minimum confidence of 60%.